2007
DOI: 10.1529/biophysj.106.103705
|View full text |Cite
|
Sign up to set email alerts
|

Two-Step Mechanism of Homogeneous Nucleation of Sickle Cell Hemoglobin Polymers

Abstract: Sickle cell anemia is a debilitating genetic disease that affects hundreds of thousands of babies born each year worldwide. Its primary pathogenic event is the polymerization of a mutant, sickle cell, hemoglobin (HbS); and this is one of a line of diseases (Alzheimer's, Huntington's, prion, etc.) in which nucleation initiates pathophysiology. We show that the homogeneous nucleation of HbS polymers follows a two-step mechanism with metastable dense liquid clusters serving as precursor to the ordered nuclei of t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

11
120
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
4

Relationship

1
9

Authors

Journals

citations
Cited by 107 publications
(131 citation statements)
references
References 76 publications
(104 reference statements)
11
120
0
Order By: Relevance
“…We stress that, although the oligomers that form because of attractive nonspecific interactions are rare (and therefore, hard to observe directly), their formation is a crucial onpathway step in the amyloid formation process for peptides with a β-competent state that is not particularly stable. Similar 2SN processes involving amorphous precursors have been identified in very different physical phenomena, such as protein crystal nucleation (67), nucleation of sickle cell hemoglobin polymers (68), and biomineralization (69). The surprising finding of this work is that, at realistic (i.e., low) peptide concentrations, fibril formation must proceed through an intermediate amorphous oligomer and that this pathway leads to highly nontrivial predictions for the dependence of the critical nucleus size and nucleation barrier on monomer concentration and interpeptide interaction.…”
Section: Discussionmentioning
confidence: 57%
“…We stress that, although the oligomers that form because of attractive nonspecific interactions are rare (and therefore, hard to observe directly), their formation is a crucial onpathway step in the amyloid formation process for peptides with a β-competent state that is not particularly stable. Similar 2SN processes involving amorphous precursors have been identified in very different physical phenomena, such as protein crystal nucleation (67), nucleation of sickle cell hemoglobin polymers (68), and biomineralization (69). The surprising finding of this work is that, at realistic (i.e., low) peptide concentrations, fibril formation must proceed through an intermediate amorphous oligomer and that this pathway leads to highly nontrivial predictions for the dependence of the critical nucleus size and nucleation barrier on monomer concentration and interpeptide interaction.…”
Section: Discussionmentioning
confidence: 57%
“…The procedure for determination of the fiber growth rate, R, from sequences of images of the evolution of HbS polymerization and other experimental details are discussed in Ref. 13. In the same article, it was shown that due to the slow diffusive supply of HbS molecules from the solution to the growing end of a fiber, the average growth rate of the HbS fibers is reduced, 14 in comparison to the case of oversupply of material, by a factor κ ≈ 3.…”
Section: Kinetic Model Of Hbs Polymer Fiber Growthmentioning
confidence: 99%
“…Contrary to the "nucleation theory", these phases are assumed to be stable and already exhibit the final crystal structure. After additional aggregation "postcritical nuclei" are built which form the basis for further crystal growth (Galkin et al 2007;Vekilov 2010b). Under normal gravity, the necessary transport of the building units (ions or molecules) occurs via diffusion and convection.…”
Section: Introductionmentioning
confidence: 99%